Reconstructing an Emergency Evacuation by Ground and Air the wildfire in Fort McMurray, alberta, Canada - Woo, M.; Hui, K. T. Y.; Ren, K.; Gan, K. E.; Kim, A. (2019)
The May 2016 wildfire of Northern Alberta – the costliest wildfire disaster in Canadian history to date – led to an area-wide evacuation by road and air. Traffic count and flight data were used to assess the characteristics of the evacuation, including estimating people movements by vehicle and aircraft. The vehicle counts were first compared to historic values to examine traffic patterns, and were then used to create an evacuation response curve, revealing an expected “S-curve” shape and highlighting how quickly the evacuation occurred. Finally, aircraft data was combined with the vehicle data to construct a cumulative curve of evacuees leaving the region. This study identified several key implications for evacuation planning and operations. The decision to evacuate residents to temporary shelters in the north was instrumental in quickly removing everyone from immediate danger using all possible exits. While unplanned contraflow added roadway capacity out of Fort McMurray, the secondary route was underutilized, suggesting that traffic routing management may reduce congestion. The evacuation response curve emphasized the volatility of wildfires, with resulting evacuations occurring under greater immediacy than hurricane evacuations. Finally, air transportation played a significant role in this evacuation, indicating that multimodal emergency evacuation plans may be critical for remote communities and sparse networks. These findings may be applied to evacuation planning and policy, to improve their efficiency and efficacy. This study contributes to the evacuation literature by providing a comprehensive empirical analysis of a wildfire evacuation by ground and air, which to our knowledge has not been conducted before.